Hierarchical Self‐Assembly of PDMA‐b‐PS Chains into Granular Nanoparticles: Genesis and Fate. Issue 23 (27th October 2014) - Bianchi, Alberto; Mauri, Michele; Bonetti, Simone; Koynov, Kaloian; Kappl, Michael; Lieberwirth, Ingo; Butt, Hans‐Jürgen; Simonutti, Roberto
<x xml:space="preserve">Abstract</x> The hierarchical self‐assembly of an amphiphilic block copolymer, poly(N, N‐dimethylacrylamide)‐block‐polystyrene with a very short hydrophilic block (PDMA10‐b‐PS62), in large granular nanoparticles is reported. While these nanoparticles are stable in water, their disaggregation can be induced either mechanically (i.e., by applying a force via the tip of the cantilever of an atomic force microscope (AFM)) or by partial hydrolysis of the acrylamide groups. AFM force spectroscopy images show the rupture of the particle as a combination of collapse and flow, while scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of partly hydrolyzed nanoparticles provide a clear picture of the granular structure. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>